The social labs revolution : a new approach to solving our most complex challenges - Hassan, Zaid (BK currents book., 2014)
Current responses to our most pressing societal challenges--from poverty to ethnic conflict to climate change--are not working. These problems are incredibly dynamic and complex, involving an ever-shifting array of factors, actors, and circumstances. They demand a highly fluid and adaptive approach, yet we address them by devising fixed, long-term plans. Social labs, says Zaid Hassan, are a dramatically more effective response. Social labs bring together a diverse a group of stakeholders--not to create yet another five-year plan but to develop a portfolio of prototype solutions, test those solutions in the real world, use the data to further refine them, and test them again. Hassan builds on a decade of experience--as well as drawing from cutting-edge research in complexity science, networking theory, and sociology--to explain the core principles and daily functioning of social labs, using examples of pioneering labs from around the world. He offers a new generation of problem solvers an effective, practical, and exciting new vision and guide.